Political Connections and Real Earnings Management: The Moderating Role of Family Ownership and Audit Quality in Indonesian Manufacturing Firms - Maeza, Muhammad Farel; Suranta, Eddy (Yayasan Ilomata, 2025)
This study investigates how political connections influence real earnings management (REM) in Indonesian manufacturing firms, considering the moderating roles of family ownership and audit quality. Using panel data regression on financial statements from companies listed on the Indonesia Stock Exchange (2020–2022), the results show that political connections do not significantly affect abnormal production costs, but they do increase REM, especially through operating cash flows and discretionary expenditures. The impact of political connections on REM is stronger in family-owned firms, particularly regarding discretionary spending. High audit quality, measured by the presence of Big Four auditors, reduces REM related to production costs but has a limited effect on cash flows and discretionary expenditures. These findings support agency theory, highlighting the need for increased external monitoring and transparency. Theoretically, this study contributes to understanding the interaction between political ties, family ownership, and audit quality in shaping earnings management behavior. Practically, the results suggest that regulators and investors should pay closer attention to politically connected, family-owned firms due to their higher risk of earnings manipulation.